2021
DOI: 10.1177/15330338211027923
|View full text |Cite
|
Sign up to set email alerts
|

A Novel miRNA-Based Model Can Predict the Prognosis of Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most prevalent renal malignant cancer, whose survival rate and quality of life of patients are still not satisfactory. Nevertheless, the TNM staging system currently used in clinical cannot make accurate survival predictions and precise treatment decisions for ccRCC patients. Therefore, there is an urgent need for more reliable biomarkers to identify high-risk subgroups of ccRCC patients to guide timely intervention and treatment. Recently, MiRNAs have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…hsa-mir-146a is involved in posttranscriptional immune regulation of gene expression in multicellular organisms by affecting mRNA stability and translation. Some of the targets of its encoded miRNAs are tumor necrosis factor, interleukin-1 receptor-associated kinase 1, leukocyte Transcripts of interleukin 1-β, TNF receptor-related factor 6, and complement factor H. Thus, low expression of hsa-mir-146a can cause tumor cells to be unrecognized causing immune evasion and reducing inflammatory responses [ 51 ]. Both Shen et al and Pastrello et al have found hasmir-146a association with the early onset of familial breast and ovarian cancer and the passible mechanism is through BRCA1/2 mRNA expression regulation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hsa-mir-146a is involved in posttranscriptional immune regulation of gene expression in multicellular organisms by affecting mRNA stability and translation. Some of the targets of its encoded miRNAs are tumor necrosis factor, interleukin-1 receptor-associated kinase 1, leukocyte Transcripts of interleukin 1-β, TNF receptor-related factor 6, and complement factor H. Thus, low expression of hsa-mir-146a can cause tumor cells to be unrecognized causing immune evasion and reducing inflammatory responses [ 51 ]. Both Shen et al and Pastrello et al have found hasmir-146a association with the early onset of familial breast and ovarian cancer and the passible mechanism is through BRCA1/2 mRNA expression regulation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, hsa-mir-146a and hsa-mir-3170 have been identified as being associated with uterine endometrial carcinogenesis and progression, and as independent predictors of overall survival in uterine endometrial cancer patients [ 50 ]. hsa-mir-3614 can directly target upstream genes to promote cancer cell proliferation and invasion, and its role in renal clear cell carcinoma and non-small-cell carcinoma has been confirmed [ 51 , 52 ]. Similar to our study, Lu et al also pointed out that has-mir-3614 is low-expressed in endometrial cancerous tissue [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to improve the diagnostic accuracy and guide the choice of treatment for KIRC patients based on the TNM staging system. Several polygenic risk models have been explored, such as the miRNA model [ 7 ], glycolysis-related gene signature [ 8 ], and metabolism-related gene signature [ 9 ]. There are different advantages and limitations in these risk models; therefore, the establishment of new biomarkers and prognostic models are required for KIRC patients.…”
Section: Introductionmentioning
confidence: 99%